PENERAPAN MOTODE EKSPERIMEN UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MENCAMPUR WARNA DI KELAS III SDN 145 MARPOYAN DAMAI KECAMATAN MARPOYAN DAMAI PEKANBARU - Putra, Juni Aidil; Antosa, Zairul; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: Background This study was caused by a teacher who did not master theother skills such as art, dance and music arts in art lessons in school culture andskills in accordance with a predetermined syllabus and the teacher does not fullyimplement the cultural art lessons and skills they know so far, especially thevisual arts. In the application of this experimental method melakuakan invitedstudents and found that students of color can be more active and creative in thelearning process. This research in the form of Classroom Action Research (CAR)with research subjects Elementary School third-grade students 145 MarpoyanPeace Pekanbaru academic year 2011/2012 conducted by 2 cycles, in each cyclewas held 2 meetings. The purpose of this research is to improve the ability ofstudents to the application of the experimental method in class III mix colors SDN145 Marpoyan Peace Pekanbaru. The results of this study showed that theaverage percentage of all teachers in the first cycle is the first meeting and thesecond meeting 60% increased by 64%, in the third meeting of the second cycle80% rise in pertemuankeempat 92%. While the percentage of students in the firstcycle of activity first meeting and the second meeting 60% up 65%, in the secondcycle is 70% and the third meeting of the fourth meeting rose 90%. While theresults of the assessment process is also seen in the first cycle there is an increasein the percentage of 40% at the first meeting and the second meeting up 46%, andthe second cycle and the third meeting 48% rise in fourth meeting 49%. While theresults of product assessment can also be seen there is an increase in the firstcycle with a percentage of 29% at the first meeting and the second meeting rose30%, and the second cycle and the third meeting 31% rise in fourth meeting 32%.This means the application of experimental methods to improve students' ability tomix colors in class III Elementary School 145 marpoyan peaceful, peacefulmarpoyan pekanbaru districts.Keywords : Methods Ekspeimen, ability to mix colors